HUSSERL AND REINACH, THE IDEA OF PROMISE - Cadena, Nathalie Barbosa de La (Revista Ética e Filosofia Política, 2017)
In this paper, I discuss the possibility of reading the description of promise presented by Reinach in The A priori Foundations of the Civil Law under the light of Husserl’s Ideas I. In order to present my argument, first, I briefly present the phenomenological method proposed by Husserl in Ideas I highlighting eidetic reduction. Second, I present the Reinachian description of social acts emphasizing the act of promising. Third, and finally, I try to demonstrate that the Reinachian description of the social act of promising is the description of a universal and necessary relation, a synthetic and a priori statement and corresponds to the idea of promise.